Teori Hukum Moral dan Tindak Korupsi di Indonesia - Tony Rachardiyanto; Markus Suryoutomo (Prosiding Seminar Nasional Ilmu Hukum, 2024)
Corruption is a problem in every country. Corruption has a negative impact on the order of national and state life. Therefore, the United Nations has established the 2003 UN Convention Against Corruption which must be ratified by every country. Indonesia has a corruption problem that is no less complicated. Basically, every corruption is under the same authority, namely the use of office by individuals to benefit themselves or their groups by deviating from the oath of office and the law. Corruption, although considered soft power, its destructive power is no less than the threat of hard power, such as ongoing collective violent conflict, separatism, or even war. This reality will be exacerbated when corruption is carried out using the law as a tool. Become a perfect crime with the legal knowledge and power possessed. It is not surprising that the law is used as a tool of crime (law as a tool of crime) which can hide corruption in the policies that cover it. Most perpetrators of corruption come from the middle class or educated people. One group with higher education and a stable profession or career.